Kinetics and Photophysical Behavior of the P,N-Rei Complex [P,N-{(C6h5)2(C5h4n)P}Re(Co)3(O-O3scf3)]: A Directly Coordinated (and Labile) Triflate - Hermosilla-Ibanez, P; Hermosilla-Ibanez, P (Elsevier Ltd, 2017)
The reaction of [P,N-{(C6H5)2(C5H4N)P}Re(CO)3Br] (RePNBr) with silver triflate leads to the complex [P,N-{(C6H5)2(C5H4N)P}Re(CO)3(O-CF3SO3)] (RePNTfO) with moderate yield. This new P,N-ReI triflate compound contains the anion directly coordinated to the metal, completing an octahedral environment. RePNTfO displays in dichloromethane (DCM) solution an irreversible oxidation about +1.35 V and three irreversible reduction processes at −1.38 V, −2.03 V and −2.30 V. Oxidation has been attributed to the ReI/ReII couple, while the reduction corresponds to PN-ligand processes, which is consistent with those computed by means of DFT. The absorption spectrum of RePNTfO in DCM displays a maximum at 295 nm (ε = 7.1 × 103 M−1 cm−1) and a shoulder around 350 nm (ε = 1.8 × 103 M−1 cm−1), which have been assigned to intraligand (π → π∗) and metal to ligand charge transfer (MLCT, dπ → π∗) transitions with the help of DFT/TDDFT. Excitation of RePNTfO in DCM at 350 nm leads to an emission spectrum centered at 535 nm. The analysis of the variation of the absorption and emission spectra in coordinating solvents compared to non-coordinating DCM, DFT/TDDFT calculations modeling and ELF analysis suggests for coordinating solvents that triflate ligand is replaced in the coordination sphere of ReI in solution. Kinetics of the exchange of triflate by bromide measured in DCM at different temperatures allowed to estimate the Eyring parameters: ΔH≠, ΔS≠ and ΔG≠, 50.8 kJ mol−1, −109.6 J K−1 mol−1 and 83.5 kJ mol−1 respectively. The high negative entropy is indicative of a compact transition state, compatible with an associative mechanism, Ia, for the exchange. © 2017 Elsevier Ltd